Combining chemotherapy with immunotherapy to treat mesothelioma: an investigation into the role of CD4+ T cells in a murine model - Steer, Henry John (2013)
Cytotoxic chemotherapy remains the mainstay of treatment for patients with cancer, however immunotherapy is starting to emerge as an additional modality of treatment. Evidence suggests that chemotherapy can synergise with immunotherapy to improve responses. Although CD8 T cells have been regarded as the main anti-tumour effector cell, the role of CD4 T cells in orchestrating CD8 and other anti-tumour responses is increasingly recognised. However, the CD4 T cell population contains effector and suppressive subsets with diverse and opposing functions. This thesis describes the establishment of a murine mesothelioma model with which to study the effects of different CD4 subsets on anti-tumour immune responses, and investigate their capacity to provide cognate help to tumour antigen specific CD8 T cells. Haemagluttin (HA) specific CD4 T cells from transgenic mice were polarised in vitro into Th1, Th2, Th17 and Treg subsets and adoptively transferred alongside HA specific CD8 T cells into mice bearing HA expressing tumours derived from a mesothelioma cell line. The effects of the different CD4 subtypes on tumour growth and their capacity to provide ‘help’ to CD8 T cells was investigated in a prophylactic treatment model and in the context of treatment with gemcitabine chemotherapy. Results showed that survival and behaviour of in vitro differentiated CD4 subtypes after adoptive transfer was highly variable and that only Th1s displayed anti-tumour activity when injected prophylactically, prior to tumour inoculation. Cytotoxic chemotherapy did not provide a favourable environment for adoptive transfer of in vitro differentiated CD4 cells. No antitumour activity was seen against established tumours, which may have been due to overriding tumour induced immunosuppressive mechanisms. Successful treatment of established tumours that had been treated with chemotherapy required both the provision of HA specific CD8 cells and the prior removal of an established, endogenous regulatory CD4 T cell population.